Violencia política en las elecciones subnacionales mexicanas. El caso de Chiapas en 2015 - Torres Alonso, Eduardo (2016)
This document presents a revision of the process that has permitted to establish in Mexico the equality in the candidacies for the relative majority principles and proportional representation to the House of Representatives, the Senate of the Republic and local congresses, and it analyses the phenomenon of political violence that some candidacies suffered during the elections on July 20th, 2015, in Chiapas.